2011
DOI: 10.1055/s-0030-1260757
|View full text |Cite
|
Sign up to set email alerts
|

SnCl2/KI-Mediated Allylation Reactions of Formaldehyde in Water

Abstract: An efficient procedure for SnCl 2 /KI-mediated allylation reactions of formaldehyde with a variety of allylic bromides in aqueous solution is reported. Under conditions developed in this effort, various homoallylic alcohols and 2-halohomoallylic alcohols are produced in good to excellent yields.Formaldehyde is an excellent electrophile for one-carbon elongation of organic substances. However, the intrinsic propensity of formaldehyde monomer to undergo polymerization dramatically limits its synthetic utility. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…2-Phenyl-but-3-en-1-ol 14 was converted to 1k (120 mg, 56% yield, clear oil). 1 H NMR (400 MHz, CDCl 3 ) δ 7.60 (d, J = 8.0 Hz, 2H), 7.37-7.19 (m, 7H), 6.93 (s, 1 H), 6.02-5.90 (m, 1 H), 5.16-5.07 (m, 2H), 4.31 (d, J = 10.0 Hz, 2H), 3.76-3.68 (m, 1H), 2.42 (s, 3H); 13 C NMR (75.5 MHz, CDCl 3 ) δ 144.7, 140.3, 137.8, 133.3, 129.5, 128.5, 128.4, 128.0, 126.8, 116.5, 79.7, 48.2, 21.6; IR (thin film) 3223, 2960, 1453, 1336, 1167, 1091, 918, 757 cm −1 ; HRMS (ESI) calcd for [M+Na] + C 17 H 19 O 3 N 1 Na 1 S 1 : 340.0969, found: 340.0978.…”
Section: Methodsmentioning
confidence: 99%
“…2-Phenyl-but-3-en-1-ol 14 was converted to 1k (120 mg, 56% yield, clear oil). 1 H NMR (400 MHz, CDCl 3 ) δ 7.60 (d, J = 8.0 Hz, 2H), 7.37-7.19 (m, 7H), 6.93 (s, 1 H), 6.02-5.90 (m, 1 H), 5.16-5.07 (m, 2H), 4.31 (d, J = 10.0 Hz, 2H), 3.76-3.68 (m, 1H), 2.42 (s, 3H); 13 C NMR (75.5 MHz, CDCl 3 ) δ 144.7, 140.3, 137.8, 133.3, 129.5, 128.5, 128.4, 128.0, 126.8, 116.5, 79.7, 48.2, 21.6; IR (thin film) 3223, 2960, 1453, 1336, 1167, 1091, 918, 757 cm −1 ; HRMS (ESI) calcd for [M+Na] + C 17 H 19 O 3 N 1 Na 1 S 1 : 340.0969, found: 340.0978.…”
Section: Methodsmentioning
confidence: 99%
“…Ethyl ester 20 was chemoselectively converted to Weinreb amide 21 . The reaction of 21 with the alkenyllithium derived from alkenyl iodide 22 furnished ketone 23 in moderate yield . Ring-closing metathesis of 23 with the second-generation Grubbs catalyst and 2,6-dichloro-1,4-benzoquinone formed the fused bicyclic skeleton, giving enone 24 in good yield .…”
mentioning
confidence: 99%
“…The general method most often utilized for the synthesis of allenylmethyl aryl ethers begins with an allenylmethyl bromide, prepared from 2-butyne-1,4-diol, as shown in Scheme . , However, several drawbacks are associated with this method, including difficult separation of the monochloro propargylic alcohol intermediate from the dichloroalkyne byproduct and the need to handle large quantities of lithium aluminum hydride. In recent studies, we observed that allenes are produced as side products in metal-mediated 2-haloallylation reactions of formaldehyde. This finding stimulated an investigation aimed at the development of metal-mediated dehalogenation reactions of vicinal dihalides ( 1 , Scheme ) as a method to generate allenes.…”
mentioning
confidence: 99%